2016
DOI: 10.1002/slct.201601180
|View full text |Cite
|
Sign up to set email alerts
|

The Green Attitude in Art Conservation: Polyhydroxybutyrate–based Gels for the Cleaning of Oil Paintings

Abstract: Fully biodegradable novel bio‐based organogels were developed for removing aged protective films from the surfaces of paintings, aiming at providing effective cleaning tools, easily controllable by reducing the solvent permeation into underlying paint layers and not dangerous for human health and the environment. The gels were based on poly‐3‐hydroxybutyrate (PHB) as gelling agent, γ‐valerolactone (GVL) as solvent and triethyl citrate (TEC) as plasticizer. PHB‐gels were able to completely remove protective var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
(29 reference statements)
2
33
0
Order By: Relevance
“…A full analytical characterization of gels similar to the one tested in this research and the biodegradability test of their components were reported by Samorì and co-workers [30]. The results demonstred that a thermoreversible physical gel was formed, exploiting the ability of the polymer to crystallize and swell in the presence of appropriate solvents such as GVL.…”
Section: Phb-gvl Characterisationsupporting
confidence: 65%
See 3 more Smart Citations
“…A full analytical characterization of gels similar to the one tested in this research and the biodegradability test of their components were reported by Samorì and co-workers [30]. The results demonstred that a thermoreversible physical gel was formed, exploiting the ability of the polymer to crystallize and swell in the presence of appropriate solvents such as GVL.…”
Section: Phb-gvl Characterisationsupporting
confidence: 65%
“…Superficial analysis on mock ups were acquired in the range of 4000-675 cm −1 on untreated and treated areas with an ATR equipped with a germanium crystal, a spectral resolution of 4 cm −1 and an optical aperture of 200 × 200 μm 2 . The solvent fraction retained by the paint layer after cleaning was determined by gas chromatographymass spectrometry analysis using headspace solid phase micro extraction (HS-SPME) sampling method [30]. A Carboxen/Polydimethylsiloxane fibre was directly exposed in the headspace of sealed vials containing the sample fragment collected from treated areas at fixed times (1 h, 24 h, and 3 days after cleaning).…”
Section: Evaluation Of the Cleaning Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…To introduce powerful and sustainable alternatives for cleaning artworks, we have recently proposed new biocompatible cleaning systems for paintings based on the use of fully green components [20,21]. In particular, in the previous researches we have demonstrated the efficiency of poly-3-hydroxybutyrate (PHB)-based gels with γ-valerolactone (GVL) as solvent, for the removal of terpenic and synthetic varnishes from oil and water sensitive egg tempera paintings [20,21].…”
Section: Introductionmentioning
confidence: 99%